Kształcenie przyszłych nauczycieli matematyki - wyzwanie edukacyjne - Żeromska, Anna K. (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
The purpose of this paper is to draw attention to the still current (as compared to the reform of higher education) issue: how should we train mathematics teachers in order to attain the desired outcomes? The article presents an extensive range of thought-provoking questions about what knowledge of well-educated mathematics teachers should be. References to the already existing didactic literature are included. Reflections on this question, containing some arguments as to the direction of the desired changes are presented. In support of these statements, two studies were carried out among students acting as teachers. Both studies point to the specificity of the necessary mathematical knowledge of teachers, and especially their need to have some flexibility in the transition from higher mathematics to school mathematics and vice versa.ddd